Pengembangan e-modul teknik highlight pada pembelajaran pewarnaan rambut - Winona, Anmel Byilmi; Hidayah, Nurul; Supiani, Titin (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
This research uses a research and development model with a 4D development model. (define, design, develop, disseminate). This research developed a highlighting hair coloring technique e-module that aims as a learning medium for hair colouring courses. As for data gathering techniques using angket spread (questioning) with qualitative and quantitative data analysis techniques. The results of the study show that the result of the material expert at stage I is 89% and at stage II is 90% with the final result is 89.5%. Based on the assessment, the e-module hair coloring technique highlight used as a learning medium is valid and “Very worthy”.